The Roles of Theory of Planned Behaviour as Motivational Factors that influencing Knowledge- Sharing Behaviour among Academicians: A Review - Ismail, Zuraima Elza; Ulan, Jusphine Owen; Omar, Arenawati Sehat (School of Social Sciences, USM, 2017)
Knowledge management is an important factor that can influence the success of organizational operations. This makes it apparent as well that there is a need to establish knowledge sharing within an organization. Promoting a knowledge-sharing behaviour is a challenge for most knowledge-savvy organizations, including educational institutions. Developing a behaviour which values and practices knowledge sharing is an effort involving attention to organizational and academicians perspective and performance. The academicians need to be emphasizing towards the sharing knowledge because the academicians are the knowledge disseminator to their students, in which knowledge-sharing in educational institutions can contribute to the success of the institutions in which it can help to develop and improve the systems as well a good quality of education in the institutions. As such, understanding motivational factors that may influence knowledge-sharing behaviour among academicians constitutes an important area of research. In an organization with knowledge sharing culture, people would share their ideas and exchange knowledge with others because they treat this culture as natural, rather than they are force to share their knowledge with others. The selected literature reveals that there are two key motivational factors: subjective norm and perceived behavioural control.